Electrochemically enabled rhodium-catalyzed [4 + 2] annulations of arenes with alkynes - Wang, Zi-Chen; Li, Rui-Tao; Ma, Qiang; Chen, Jia-Yi; Ni, Shao-Fei; Li, Ming; Wen, Li-Rong; Zhang, Lin-Bao (Green chemistry : an international journal and green chemistry resource : GC, 2021)
Herein, electrochemically driven, Rh( iii )-catalyzed regioselective annulations of arenes with alkynes have been established. The strategy, combining the use of a rhodium catalyst with electricity, not only avoids the need for using a stoichiometric amount of external oxidant, but also ensures that the transformations proceed under mild and green conditions, which enable broad functional group compatibility with a variety of substrates, including drugs and pharmaceutical motifs. Moreover, the electrolysis reaction was made operationally simple by employing an undivided cell, and proceeds efficiently in aqueous solution in air. Herein, electrochemically driven, Rh( iii )-catalyzed regioselective annulations of arenes with alkynes have been established.